1996
DOI: 10.1111/j.1365-2389.1996.tb01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate speciation in excessively fertilized soil: a 31P and 27Al MAS NMR spectroscopy study

Abstract: Both P and A1 MAS NMR spectra of samples of excessively fertilized sandy soil provided information about the P and A1 speciation. Peak deconvolution was used to interpret reliably and quantitatively the 31P NMR spectra recorded. Most of the P was found to be associated with Al. Part of the P exhibited a chemical shift that could be attributed to octocalcium phosphate, amorphous calcium phosphate or apatite. Apatite has, however, never been reported to occur in sandy soils of temperate climates. A dithionite ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…Due to higher weathering, general expectation was the lower content of lithogenic Ca-P as the primary phosphorus minerals (Cross and Schesinger, 1995) in the region than the soils of sourh of Iran, the opposite trend is probably an effect of intensive application of inorganic P fertilizer. It has been reported heavily fertilized acid soils may contain significant amounts of Ca phosphates (Lookman et al, 1996), and hydroxyapatite has been found as a product of the dissolution of superphosphates in acid and slightly acidsoils (Kumar et al, 1994). The least content of HCl-P was belong to soil 2 (pH=5.83) …”
Section: Lithogenic Ca-pmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to higher weathering, general expectation was the lower content of lithogenic Ca-P as the primary phosphorus minerals (Cross and Schesinger, 1995) in the region than the soils of sourh of Iran, the opposite trend is probably an effect of intensive application of inorganic P fertilizer. It has been reported heavily fertilized acid soils may contain significant amounts of Ca phosphates (Lookman et al, 1996), and hydroxyapatite has been found as a product of the dissolution of superphosphates in acid and slightly acidsoils (Kumar et al, 1994). The least content of HCl-P was belong to soil 2 (pH=5.83) …”
Section: Lithogenic Ca-pmentioning
confidence: 99%
“…In acid to neutral soils, Fe and Al phosphates are the typical precipitation products (Lindsay, 1979;Pierzynski et al, 1990;Cross and Schlesinger, 1995). However, some heavily fertilized acidic soils contain significant amounts of Ca phosphates (Lookman et al, 1996), and hydroxyapatite has been found as a product of the dissolution of superphosphates in acidic and slightly acidic soils (Kumar et al, 1994). Pierzynski et al (1990) showed that P-rich particles resulting from fertilizer dissolution in acid soils included not only Al and Fe but also Si and Ca.…”
Section: -mentioning
confidence: 99%
“…Solid-state 27 Al NMR may be used to determine Al-coordination in Al-bearing minerals like phyllosilicates or allophanes (Goodman et al, 1985;Kinsey et al, 1985;Ildefonse et al, 1994) and even in soil samples, despite peak broadening or signal loss due to the existence of nonsymmetric Al-environments and the presence of paramagnetic species such as iron oxides and substituted Fe 3+ (Wilson et al, 1984). Further information may be obtained, including the interactions of aluminum with phosphate groups and Al speciation in highly fertilized sandy soils (Lookman et al, 1996) or the degree of polymerization of imogolite-like structures in andosols (BasileDoelsch et al, 2005). Original information on organo-Al complexes has been obtained by liquid-state 27 Al NMR, either in the case of small organic acids (Masion et al, 1994;Jordan et al, 1996;Thomas et al, 1997) or humic acids (Lu et al, 1999;Hiradate and Yamaguchi, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…This requires a degree of operator input, in particular to determine the number and characteristics of the deconvoluted peaks, but it more accurately quantifies signals from individual compounds where these can be identified using authentic standards. Deconvolution has rarely been used to study soils, although 13C CP-MAS spectra of decayed wood, dissolved organic carbon, and fresh cedar foliage (Davis et al, 1994;Wershaw et al, 1996;Preston, 2001), and solidstate 31P spectra of agricultural soils (Lookman et al, 1996;McDowell et al, 2002) have all been investigated using the technique. In this study we demonstrate the application of the deconvolution procedure to the determination of myo-inositol hexakisphosphate in a range of permanent lowland pasture soils from England and Wales, and we use this information to explore the factors controlling myo-inositol hexakisphosphate accumulation in the soil environment.…”
mentioning
confidence: 99%